2011
DOI: 10.1186/1471-2377-11-47
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate monitoring on the stroke unit. What does heart beat tell about prognosis? An observational study

Abstract: BackgroundGuidelines recommend maintaining the heart rate (HR) of acute stroke patients within physiological limits; data on the frequency and predictors of significant deviations from these limits are scarce.MethodsDemographical data, stroke risk factors, NIH stroke scale score, lesion size and location, and ECG parameters were prospectively assessed in 256 patients with ischemic stroke. Patients were continuously monitored for at least 24 hours on a certified stroke unit. Tachycardia (HR ≥120 bpm) and bradyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The causes of higher admission pulse rate are the large stroke, severe stroke (NIHSS >15), and atrial fibrillation. [ 16 ] The data from this study corroborate with Böhm et al . who reported in their study that faster admission heart rate predicts the mortality and poor functional outcome in a patient with acute ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…The causes of higher admission pulse rate are the large stroke, severe stroke (NIHSS >15), and atrial fibrillation. [ 16 ] The data from this study corroborate with Böhm et al . who reported in their study that faster admission heart rate predicts the mortality and poor functional outcome in a patient with acute ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of these arrhythmias was highest in the first 24 hours and de clined over 3 days. 332 Ritter and colleagues 333 conducted a prospective study of 256 patients with ischemic strokes who were continuously monitored for at least 24 hours. In this study, 15% had episodes of a heart rate >120 bpm; this was associated with larger lesion size, higher National Institutes of Health Stroke Scale score, and AF.…”
Section: Strokementioning
confidence: 99%
“…After activation, the nursing staff performs a standard ECG and calls the neurologist to evaluate the patient's condition. 28,29 A recent meta-analysis of studies with varying durations of cardiac monitoring showed the overall detection rate of any AF after a transient ischaemic attack or a brain infarction was 11.5%, although there was high variability due to the varying sensitivities of the diagnostic tools. 21 The detection rate of inpatient cardiac monitoring in selected patients is 6.5-21.3%, 25,30,31 which is slightly lower than the 26.3% rate of AF in our study.…”
Section: Discussionmentioning
confidence: 99%